2022
DOI: 10.1002/dad2.12326
|View full text |Cite
|
Sign up to set email alerts
|

Exploring discordant low amyloid beta and high neocortical tau positron emission tomography cases

Abstract: Introduction Neocortical 3R4R (3‐repeat/4‐repeat) tau aggregates are rarely observed in the absence of amyloid beta (Aβ). 18 F‐MK6240 binds specifically to the 3R4R form of tau that is characteristic of Alzheimer's disease (AD). We report four cases with negative Aβ, but positive tau positron emission tomography (PET) findings. Methods All Australian Imaging, Biomarkers and Lifestyle study of aging (AIBL) study participants with Aβ ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Additional genetic and biofluid analyses, and ultimately autopsy data, will be helpful to better interpret these PET results and clarify the underlying cause of cognitive impairment in these patients. A likely hypothesis, supported by Krishnadas et al., 47 is that these patients could have underlying AD with a false negative amyloid‐PET due to a relative low burden of neuritic plaques 39 or rare Aβ conformation that are not detected by the radiotracer 48–51 . Alternatively, PET results could reflect a false positive tau‐PET or a true tau tangle‐only disease, such as primary age‐related tauopathy 52 or MAPT variants associated with tau‐PET‐positive Frontotemporal lobar degeneration (FTLD)‐tauopathy 53 …”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Additional genetic and biofluid analyses, and ultimately autopsy data, will be helpful to better interpret these PET results and clarify the underlying cause of cognitive impairment in these patients. A likely hypothesis, supported by Krishnadas et al., 47 is that these patients could have underlying AD with a false negative amyloid‐PET due to a relative low burden of neuritic plaques 39 or rare Aβ conformation that are not detected by the radiotracer 48–51 . Alternatively, PET results could reflect a false positive tau‐PET or a true tau tangle‐only disease, such as primary age‐related tauopathy 52 or MAPT variants associated with tau‐PET‐positive Frontotemporal lobar degeneration (FTLD)‐tauopathy 53 …”
Section: Discussionmentioning
confidence: 81%
“…See Table S4 and Figure S3 for statistical comparisons. EOAD, early-onset Alzheimer's disease; EOnonAD, early-onset non-Alzheimer's disease; PCA, posterior cortical atrophy; PET, positron emission tomography; PPA, primary progressive aphasia; SUVR, standardized uptake value ratio et al, 47 is that these patients could have underlying AD with a false negative amyloid-PET due to a relative low burden of neuritic plaques 39 or rare Aβ conformation that are not detected by the radiotracer. [48][49][50][51] Alternatively, PET results could reflect a false positive tau-PET or a true tau tangle-only disease, such as primary age-related tauopathy 52 or MAPT variants associated with tau-PET-positive Frontotemporal lobar degeneration (FTLD)-tauopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have generally agreed with these findings and concluded that PART has some features in common with, but is distinct from, AD . However, there are critical methodologic differences in how PART is defined in neuropathologic and biomarker studies that complicate comparisons.…”
mentioning
confidence: 77%
“…Studies have generally agreed with these findings and concluded that PART has some features in common with, but is distinct from, AD. [11][12][13][14][15] However, there are critical methodologic differences in how PART is defined in neuropathologic and biomarker studies that complicate comparisons. Participants in observational studies are younger than individuals in neuropathologic cohorts, limiting direct comparison of this agerelated pathologic condition.…”
mentioning
confidence: 99%
“…Amyloid-positive patients with MCI show greater tau deposition than amyloid-negative patients with MCI, with very few individuals showing high tau deposition in the absence of amyloid deposition 33 . In fact, amyloid-negative patients with tau positivity in the cortex have recently been postulated to be false-negative amyloid PET cases 34 . Longitudinal studies have suggested that patients with MCI show a more pronounced rate of accumulation of tau relative to cognitively normal people.…”
Section: Alzheimer Diseasementioning
confidence: 99%